Shoreline_veget— a new shoreline extraction method for vegetation seas, with high robustness, accuracy and scalability - Weihua Li; Lianglin Liu; Wei Zhu; Jiuming Li; Teng Liu (Frontiers in Marine Science)
To address the issue of vegetation obstructing water bodies and resulting in missing information in vegetation sea areas, existing methods that focus on various types of shorelines often exhibit limited algorithm stability and accuracy. This study introduces a method, termed Shoreline_veget. The method comprises four modules: data preprocessing, point cloud boundary extraction and processing, elevation gradient function design, modified fused boundary point cloud, and tidal correction. This method can reduce the overall shoreline accuracy from 0.6658, 0.3854, and 0.4127 (as observed with three comparative methods) to 0.1531. Compared to the least accurate method, this method improved the overall shoreline accuracy by 0.5127 m. The result confirm that the proposed method offers superior stability, and this methodology provides new technology to measure, map, and manage shorelines, offers valuable insight for related research.